“Gestión de riesgos laborales en los puestos de trabajo en el área administrativa de la facultad de Ciencias políticas y administrativas de la UNACH Campus Norte Ms. Edisón Riera: Plan de Prevención de Riesgos” - Viñán Zabala, Erika Patricia (2017)
Occupational risk prevention is a key factor for every organization, to improve the employee’s performance and efficiency always taking into account their safety when performing each activity. The purpose of this research work is to perform a risk management by occupational risks identifying, measurement and evaluation in the administrative area of the Facultad de Ciencias y Administrativas of the UNACH north campus MSc. Edison Riera. An inspection and direct observation of the worker was carried out for data collection with the application of checklists in each work position. It was performed the measurement and evaluation of physical, ergonomic and psychosocial risks with the obtained results, of qualitative and quantitative form with different evaluation methods, such as the RULA method for ergonomic risks, ISTAS 21 for psychosocial risks and the implementation of Matrix of the Ministry of Labor Relations for physical risks like noise, illumination, and temperature. With the results obtained, it was determined that in Ergonomic Risks 87% of the work position evaluated have a level 2 of moderate action, because incorrect postures and repetitive movements are presented. In addition, in Psychosocial Risks in the work positions evaluated, 30% have a high level, and middle level of action, and 40% a low level due to psychological demands, insecurity and esteem. According to the results of each evaluated corrective and preventive actions were developed, which will helps us to establish control measures on them, with the purpose of reduce the damages that could happen to the worker. Therefore the proposal of a Risk Prevention Plan was presented, applying preventive measures for each work position, which seeks to reduce the risks to which may be exposed in the study area, ensuring the worker’s integrity and safety.